2019
DOI: 10.1097/ijg.0000000000001359
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Central Visual Field Defect as a Risk Factor For NTG Progression: A 5-Year Prospective Study

Abstract: Precis: This 5-year follow-up study on normal-tension glaucoma (NTG) patients demonstrated that those with baseline central visual field (VF) defect progress at a more increased rate compared with those with peripheral field defect. Purpose: The purpose of this study was to investigate the clinical characteristics, including 24-hour ocular perfusion pressure and risk of progression in patients with baseline central VF defect, as compared with those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Nevertheless, some studies reported the opposed findings; presence of hemodynamic turbulence has little to do with the location of VF defects 42 , and no significant differences were found between NTG and high tension glaucoma regarding the slopes or depths of the VF defect 43 . Moreover, no difference in systemic and vascular factors between patients with paracentral and peripheral VF defects was found 44 , 45 . Park et al 46 found totally overturned results that eyes with paracentral VFD had distinctive ocular and systemic hemodynamic features.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, some studies reported the opposed findings; presence of hemodynamic turbulence has little to do with the location of VF defects 42 , and no significant differences were found between NTG and high tension glaucoma regarding the slopes or depths of the VF defect 43 . Moreover, no difference in systemic and vascular factors between patients with paracentral and peripheral VF defects was found 44 , 45 . Park et al 46 found totally overturned results that eyes with paracentral VFD had distinctive ocular and systemic hemodynamic features.…”
Section: Discussionmentioning
confidence: 88%
“…Only central scotoma was statistically significant in the multivariate analysis. Central scotoma has been associated with vascular instability and increased risk of progression especially in NTG patients [ 25 , 26 , 27 , 28 ]. Glaucoma patients with central scotoma have been shown to have lower vascular density and greater fluctuation in vascular density as measured by OCT angiography [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study added that imaging the optic disc using OCT-A may also be important to monitor initial paracentral scotomas in glaucoma patients. Initial paracentral scotoma has been reported to be a factor related to future glaucoma progression 30 , 31 . The presence of central VF damage at baseline was significantly associated with more rapid global progression.…”
Section: Discussionmentioning
confidence: 99%